A comparative analysis of sphenoid bone between domestic sheep (ovis aries) and goat (capra hircus) using geometric morphometrics. (2nd February 2021) - Parés‐Casanova, Pere M.; Domènech‐Domènech, Xènia
Abstract: The sphenoid bone forms the rostral part of the base of the neurocranium and is composed of two segments, the presphenoid [ os praesphenoidale ] and the basisphenoid [ os basisphenoidale ]. Rarely studied in osteology, we tested whether it can provide distinctive features between domestic sheep ( Ovis aries L., 1758) and goat ( Capra hircus L., 1758). For this goal, we studied a sample comprised by 53 dry modern skulls of adult sheep ( n  = 36) and goat ( n  = 17) subjects from a modern comparative collection by means of geometric morphometric techniques using a total of 26 anatomical points (2 saggital landmarks and 24 semilandmarks). Results showed that form (size + shape) differences appear between both species: sphenoid among sheep tends to be bigger, longer and wider than in goats, differences of width being mainly located on basisphenoid width.